Правове регулювання припинення державної служби - Безкоровайний, Б. О.; Bezkorovainyi, B. O. (Вісник Харківського національного університету внутрішніх справ. – 2013. – № 2 (61). – С. 266-272, 2013)
Проаналізовано підстави припинення державної служби. Обґрунтовано висновок про застосування комплексного підходу до викладення підстав припинення державної служби з метою полегшення правозастосовної практики. Запропоновано власну редакцію ст. 30 Закону України «Про державну службу».

It is emphasized that special place, among wide range of problems of legal regulation of relations in the sphere of state service, is the problem of determining the branch belonging of the mentioned relations. It is noted that there is a need to consider this problem from the point of the unity and differentiation of legal regulation of labor relations, i.e. from the point of relations’ belonging in the sphere of state service to the sphere of labor law. Special attention is paid to the fact that legal regulation of labor legal relations’ cessation with officials is realized on the basis of the provisions of the Labor Code of Ukraine and the Law of Ukraine «About State Service» dated from December 16, 1993 № 3723-XII.

Проанализированы основания прекращения государственной службы. Обоснован вывод о применении комплексного подхода к изложению оснований прекращения государственной службы с целью облегчения правоприминительной практики. Предложена собственная редакция ст. 30 Закона Украины «О государственной службе».
Legal Regulation of the State Service’s Cessation
Правовое регулирование прекращения государственной службы
Безкоровайний, Б. О. Правове регулювання припинення державної служби / Б. О. Безкоровайний // Вісник Харківського національного університету внутрішніх справ. – 2013. – № 2 (61). – С. 266-272.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; державна служба; государственная служба; state service; трудові правовідносини; трудовые правоотношения; labor legal relations; звільнення зі служби; увольнение со службы; припинення державної служби; прекращения государственной службы; state service cessation; правове регулювання; правовое регулирование; legal regulation